1971
DOI: 10.1111/j.1469-8137.1971.tb04588.x
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation Injury in Mosses

Abstract: SUMMARYIntra-speclfic differences in desiccation injury are shown in collections of Acrocladium cuspidatum, Climadum dendroides and Hypnum cupressiforme from habitats subjected to a wide range o moisture stresses. The degree of desiccation tolerance is correlated with degree of moisture stress in the habitat. Desiccation injury was measured as the decline in the initial rate of photosynthesis on remcistening. Collections of species from habitats in which severe moisture deficits occur show a slower decline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…The same species obtained from a water seepage on a stone wall showed a desiccation resistance index of 21-6, a recovery index of 63-8 and contained 517 /^mol g~p otassium (compared to values of 76*1, 110-7 and 196 for the dry habitat sample). Lee and Stewart (1971) and Stewart and Lee (1972) have also reported that races of mosses from wet and dry habitats show differences, after desiccation, in terms of their ability to show recovery of photosynthesis and the degree to which NADP+-linked glyceraldehyde 3-phosphate dehydrogenase is stimulated by glutathione.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same species obtained from a water seepage on a stone wall showed a desiccation resistance index of 21-6, a recovery index of 63-8 and contained 517 /^mol g~p otassium (compared to values of 76*1, 110-7 and 196 for the dry habitat sample). Lee and Stewart (1971) and Stewart and Lee (1972) have also reported that races of mosses from wet and dry habitats show differences, after desiccation, in terms of their ability to show recovery of photosynthesis and the degree to which NADP+-linked glyceraldehyde 3-phosphate dehydrogenase is stimulated by glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Work on the sensitivity of bryophytes to desiccation stress has included studies of changes in photosynthetic and respiratory capacity (see Lee and Stewart, 1971;Proctor, 1974, 1976, and references therein) and the stabiHty of polyribosomes (e.g. Tucker and Bewley, 1976;Dhindsa and Bewley, 1977) in relation to depth and duration of desiccation.…”
Section: Introductionmentioning
confidence: 99%
“…The distributions of the lichen symbiotic association (Rogers, 1971) and of mosses (Lee & Stewart, 1971) have been correlated in at least some cases with desiccation tolerance. In lichens, it may be the fungal partner which is responsible for the desiccation resistance of the thallus, since fungi are able to tolerate lower water potentials than any other organisms This work was supported by a research grant from the U.S. National Science Foundation (Scott, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out on this phenomenon, and shown that, on rehydration, the gametophytes are able to recover most of their metabolic activities. Respiration and photosynthesis have been shown to resume either immediately, or a short time after the addition of water (Hinshiri and Proctor, 1971;Lee and Stewart, 1971;Bewley, Tucker and Gwozdz 1974;Bewley and Gwozdz, 1975;Bewley et al, 1978;Proctor, 1974, 1979;Peterson and Mayo, 1975;Gupta, 1976, 1977 andreferences therein). Concerning RNA metabolism, Bewley (1972Bewley ( , 1973, Tucker and Bewley (1976), Dhindsa and Bewley (1977) have pointed out, that polyribosomes are conserved during desiccation of the terrestrial moss Tortula ruralis.…”
Section: Introductionmentioning
confidence: 99%